85.5k views
4 votes
Sole the equations for (x,y) 3x+y=1 and
x-y = -5

User ToxicFrog
by
5.2k points

1 Answer

5 votes

Answer:

(- 1, 4 )

Explanation:

Given the 2 equations

3x + y = 1 → (1)

x - y = - 5 → (2)

Adding the 2 equations term by term eliminates the term in y, that is

(3x + x) + (y - y) = (1 - 5), simplifying gives

4x = - 4 ( divide both sides by 4 )

x = - 1

Substitute x = - 1 into either of the 2 equations for corresponding value of y

Substituting in (1)

3(- 1) + y = 1

- 3 + y = 1 ( add 3 to both sides )

y = 4

Solution is (- 1, 4 )

User HellGate
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.